The Relationship Between Parenting Patterns and Students' Mental Health During The Covid-19 Pandemic - Muhyani Nasukha; Revitha Almaisya; Hasan Basri Tanjung (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This study is about the relationship between parenting and student mental health during the Covid-19 pandemic at MTs Al Ahsan Bogor City, which has the goal of (1) knowing parenting, (2) knowing students' mental health during the Covid-19 pandemic, and (3) knowing the relationship of parenting with mental health. Adolescence is a period of transition from children to adulthood, many things that parents worry about when their children are already in their teenage years. With the Covid-19 pandemic, many activities were suspended while one of them was school activities. If the school switches to learning from home, then many children will take advantage of their free time to do deviant things. Because by doing deviant things will greatly affect his mental health. The influence of the family is very large in the formation of the foundation of the child's personality. In accompanying children when at home each parenting applied to their children has different effects on the level of mental health. Therefore, a good family environment will also have an impact on the soul or commonly called a healthy mentality. This research uses quantitative methods with the category of survey research (survey research). In this study in statistical tests in statistical tests, there was a significant relationship between ParentIng and Student Mental Health during the Covid-19 pandemic at MTs Al-Ahsan Bogor City. This is because the results of statistical test analysis show the value of thitung = -13,763 > ttabel = 1,972. So Ho was rejected and H1 was accepted.